PENGARUH KEBIJAKAN DIVIDEN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL MODERASI STUDI PADA PERUSAHAAN FOOD AND BEVERAGE DI BURSA EFEK INDONESIA PERIODE 2022–2024 - Entin Melanda Sari; Sri Hasnawati (Nusantara Hasana Journal, 2026)
This study aims to analyze the effect of dividend policy and capital structure on firm value with Corporate Social Responsibility (CSR) as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The study employs a quantitative approach using secondary data obtained from financial statements, annual reports, and sustainability reports. The sampling technique used purposive sampling, resulting in 28 companies as research samples with a total of 84 observations. The analysis method applied panel data regression with Moderated Regression Analysis (MRA) using EViews 13 software. The variables used in this study include dividend policy proxied by Dividend Payout Ratio (DPR), capital structure proxied by Long-term Debt to Equity Ratio (LtDER), firm value proxied by Price to Book Value (PBV), and Corporate Social Responsibility (CSR) measured using the GRI Standards 2021 disclosure index. The results indicate that dividend policy does not have a significant effect on firm value. Meanwhile, capital structure has a negative and significant effect on firm value, indicating that higher long-term debt tends to reduce firm value. Furthermore, CSR is not able to moderate the relationship between dividend policy and firm value. However, CSR is proven to moderate the relationship between capital structure and firm value by weakening the negative impact of capital structure on firm value. These findings imply that CSR disclosure plays an important role in improving investor confidence and reducing negative perceptions related to financial risk caused by high debt levels. Therefore, companies are encouraged to strengthen CSR implementation as part of their long-term strategy to enhance firm value and maintain business sustainability.